Law is discourse. Discourse is rhetoric. Therefore, Law is rhetoric. A rhetorical analysis of the responsibility to protect - El-Kassaby, Dina (AUC Knowledge Fountain, 2014)
It is estimated that the yearly cost of containing and responding to conflict worldwide is nearly US$10 trillion. Meanwhile, the level of global peace and security is on the steady decline and gross violations of human rights and massive loss of human life are not yet an issue of the past. As such, contemporary international legal doctrines like The Responsibility to Protect (R2P) have emerged in an effort to prevent and react to global conflict. This thesis performs an atypical study of R2P by performing a rhetorical analysis of the doctrine through the lens of Orientalism and post-colonial theory. In doing so, this thesis reveals the ways in which the discourse of R2P functions as a mode of reproducing and exercising power over the ‘Other’ of international law, the Orient. It also shows that the rhetorical persuasiveness of the R2P narrative is itself an Orientalist discourse that recreates and reinforces colonial binaries between the Occident and the Orient, making the Orient susceptible and subject to contemporary forms of control and domination in the name of humanitarianism. By confronting the continuing implications of colonial history on contemporary international law, this thesis has recognized and deconstructed through rational analysis the lasting psychological and legal effects of the colonial enterprise into the twenty-first century.